2010
DOI: 10.1002/btpr.394
|View full text |Cite
|
Sign up to set email alerts
|

Separation of viable and nonviable animal cell using dielectrophoretic filter

Abstract: Selective separation of cells using dielectrophoresis (DEP) has recently been studied and methods have been proposed. However, these methods are not applicable to large-scale separation because they cannot be performed efficiently. In DEP separation, the DEP force is effective only when it is applied close to the electrodes. Utilizing a DEP filter is a solution for large-scale separation. In this article, the separation efficiency for viable and nonviable cells in a DEP filter was examined. The effects of an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The first approach is electrode-based dielectrophoresis (eDEP), 29,31,36 where the frequency of AC electric fields imposed upon in-channel microelectrodes is tuned to obtain distinctive dielectrophoretic responses between live and dead cells. The result is a selective retention of one type of cells (either live or dead depending on the medium conductivity and the AC field frequency) upon the electrodes while the other type is either washed out by the medium flow [37][38][39][40][41][42][43][44][45][46] or travels itself through a stationary medium in response to a travelling electric field. 47 Such eDEP separation has also been demonstrated in the form a lateral deflection of live and dead cells to differential flow paths in the laminar medium stream, which can then be continuously sorted into separate reservoirs.…”
mentioning
confidence: 99%
“…The first approach is electrode-based dielectrophoresis (eDEP), 29,31,36 where the frequency of AC electric fields imposed upon in-channel microelectrodes is tuned to obtain distinctive dielectrophoretic responses between live and dead cells. The result is a selective retention of one type of cells (either live or dead depending on the medium conductivity and the AC field frequency) upon the electrodes while the other type is either washed out by the medium flow [37][38][39][40][41][42][43][44][45][46] or travels itself through a stationary medium in response to a travelling electric field. 47 Such eDEP separation has also been demonstrated in the form a lateral deflection of live and dead cells to differential flow paths in the laminar medium stream, which can then be continuously sorted into separate reservoirs.…”
mentioning
confidence: 99%
“…4A) was proposed by Hakoda et al. . The DEP filter was capable of selectively retaining the viable cells by negative DEP force.…”
Section: Cell Viability Assessmentmentioning
confidence: 99%
“…(A) Diagrams of DEP separation filter and DEP responses under different frequencies. Adapted with permission from , © 2010 American Institute of Chemical Engineers. (B) DEP isolation of cells using 3D castellated microelectrodes and capturing/removal efficiencies.…”
Section: Cell Viability Assessmentmentioning
confidence: 99%
“…Several studies have demonstrated the use of DEP to selectively manipulate analytically and clinically relevant cell types, such as bacteria or cancer cells. A variety of studies have focused on the DEP trapping behavior, demonstrating differences in the DEP response of cell types such as dead versus live cells [11][12][13][14] or cancer cells versus erythrocytes or T lymphocytes [15]. Consequently, cells can be sorted or fractionated according to their dielectrophoretic response.…”
Section: Introductionmentioning
confidence: 99%